Dinge - Nutzer - Netze Von der Virtualisierung des Musealen zur Musealisierung des Virtuellen - Niewerth, Dennis (Edition Museum, 2018)
Museums have always been virtual places - so why do these institutions find it so difficult to use digital media? And what does a museum have to offer to a knowledge-based society whose act of remembering increasingly takes place in the digital domain?